2017
DOI: 10.1017/aaq.2017.42
|View full text |Cite
|
Sign up to set email alerts
|

Settlement Scaling in Middle-Range Societies

Abstract: The contemporary relevance of archaeology would be greatly enhanced if archaeologists could develop theory that frames human societies of all scales in the same terms. We present evidence that an approach known as settlement scaling theory can contribute to such a framework. The theory proposes that a variety of aggregate socioeconomic properties of human networks emerge from individuals arranging themselves in space so as to balance the costs of movement with the benefits of social interactions. This balancin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 66 publications
2
25
0
Order By: Relevance
“…In contrast, Figures 1 and 2 combine sites that date to different moments in the history of each region. There is no theoretical reason to expect that the intercept of the fit line capturing the relationship between N and Y should be static, but previous studies have not found evidence for a changing intercept over time (Ortman et al, 2015Ortman and Coffey, 2017). The fact that the pooled analysis presented here leads to an estimate of β that is so close to the theoretical prediction provides additional evidence for consistency in the basic energetics of the economy in each of these regions over long periods of time.…”
Section: An Examplesupporting
confidence: 56%
See 3 more Smart Citations
“…In contrast, Figures 1 and 2 combine sites that date to different moments in the history of each region. There is no theoretical reason to expect that the intercept of the fit line capturing the relationship between N and Y should be static, but previous studies have not found evidence for a changing intercept over time (Ortman et al, 2015Ortman and Coffey, 2017). The fact that the pooled analysis presented here leads to an estimate of β that is so close to the theoretical prediction provides additional evidence for consistency in the basic energetics of the economy in each of these regions over long periods of time.…”
Section: An Examplesupporting
confidence: 56%
“…As a result, individuals in larger settlements have more social contacts and exchanges per unit time; and there are also increased opportunities for specialization as individuals can meet more of their material needs through human networks as opposed to their own individual effort. This process, which we label the "social reactor process, " induces human networks to grow in consistent, non-linear, and open-ended ways with population (Bettencourt, 2013(Bettencourt, , 2014Ortman et al, 2015Ortman et al, , 2016Cesaretti et al, 2016;Hanson et al, , 2019Ortman and Coffey, 2017).…”
Section: An Examplementioning
confidence: 99%
See 2 more Smart Citations
“…The social interactions facilitated by physical proximity-and the lower costs associated with such interactions-drive productivity (Bettencourt et al, 2008Bettencourt, 2013). These relationship have been statistically investigated not only for modern metropolitan systems (in the United States, Western Europe, Brazil, Japan, India, China and South Africa) but also for Native American farming villages in North America (before the arrival of the Europeans), Pre-Hispanic Andean and Central Mexican settlements, Ancient Greek and Roman cities, Medieval European cities and towns, and cities in Tudor England (Ortman et al, 2014(Ortman et al, , 2015Cesaretti et al, 2016;Ortman and Coffey, 2017;Ossa et al, 2017;Cesaretti et al, under review). The results show a striking similarity in scaling relationships, as predicted by the settlement scaling framework.…”
Section: The City As One Thing: a Container For "Energized Crowding"mentioning
confidence: 99%